Experimental numerical modelling of arterial grafts: Transient flow - Catarina F. Castro (2012)
The exact mechanisms causing failure of arterial bypass grafting are not yet well explained. In the present study, computational fluid dynamics techniques are applied for the simulation of blood flow in arterial grafts under physiologically realistic inflow waveforms. To ensure a realistic prediction of the flow field, a patient-specific inflow waveform is employed. The results, which are found both qualitatively and quantitatively consistent with other experimental and numerical studies, indicate that the lowest shear stress regions are found on the arterial wall opposite to the junction, which are predominantly susceptible to the occurrence of artery plaque formation diseases.